Quality Testing of Iretsu Dyeing Result on Primissima Cotton and Chiffon Fabrics Using Water Glass as a Fixator - Meishinta Alvionita Junia Mirantika; Adhi Kusumastuti (Universitas Negeri Semarang, 2026)
Textiles are essential materials for human clothing, and dyeing plays a crucial role in enhancing their aesthetic value. Textile dyeing generally employs natural and synthetic dyes. In recent years, synthetic dyes have been more widely used due to their availability, efficiency, and applicability to various fabric types. However, certain synthetic dyes are specifically designed for particular fabrics. Iretsu dye, for instance, is commonly used for polyester-based textiles. This study aimed to evaluate the dyeing quality of iretsu synthetic dye on two different fabrics, namely primissima cotton and chiffon, using two dye formulations with the same immersion time. An experimental method was employed by dyeing primissima cotton and chiffon fabrics using two dye concentrations, 12 g and 24 g, with an immersion time of 1 hour. Water glass was applied as a color fixative. The color direction of the dyed fabrics was assessed through an organoleptic test conducted by panelists consisting of 2022 cohort students of the Fashion Education Study Program, Universitas Negeri Semarang, who had completed the Textile Dyeing Techniques course. The results of the organoleptic test indicated that primissima cotton dyed with a 12 g formulation produced a pewter color direction (50%), while chiffon dyed with the same formulation resulted in a flint color direction (50%). Using the 24 g formulation, primissima cotton exhibited a porpoise color direction (55%), whereas chiffon predominantly showed a flint color direction (70%). These findings suggest that variations in dye concentration influence the resulting color direction on different fabric types when dyed with iretsu synthetic dye.